(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article discusses the manifestation of guilt feelings in students and the influence of the family environment on their development. Guilt is considered a relatively less painful emotional experience compared to shame, which is associated with the negative evaluation of one’s personal traits. Guilt is typically accompanied by feelings of repentance, apology, and remorse.